2022
DOI: 10.3390/pr10112466
|View full text |Cite
|
Sign up to set email alerts
|

Pollution Dispersion and Predicting Infection Risks in Mobile Public Toilets Based on Measurement and Simulation Data of Indoor Environment

Abstract: Since the 21st century, in several public health emergencies that have occurred across the world, the humid enclosed environment of the toilet has become one of the places where bacteria, viruses, and microorganisms breed and spread. Mobile public toilets, as a supplement of urban fixed public toilets, are also widely used in densely populated areas. According to statistics, since the outbreak of COVID-19 in 2019, multiple incidents of people being infected by the COVID-19 virus due to aerosol proliferation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The ventilation system has a significant impact on the distribution of pollutant concentrations in the toilet. The upper supply and down exhaust are the best for pollutant emissions from mobile public toilets [33]. What is more, forced ceiling supply and wall exhaust systems proved to be the optimal ventilation systems for bathrooms [25].…”
Section: Discussion Of the Air Quality Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…The ventilation system has a significant impact on the distribution of pollutant concentrations in the toilet. The upper supply and down exhaust are the best for pollutant emissions from mobile public toilets [33]. What is more, forced ceiling supply and wall exhaust systems proved to be the optimal ventilation systems for bathrooms [25].…”
Section: Discussion Of the Air Quality Improvementmentioning
confidence: 99%
“…Zhao et al [32] compared the effects of a primary air fan-coil system and an all-air air conditioning system on indoor pollutant diffusion and found that the ventilation design of an all-air air conditioning system with an exhaust height of 400 mm can remarkably improve the indoor environmental health and ventilation efficiency of public toilets. Li et al [33] concluded based on CFD analysis that the pollution emission from mobile public toilets is best done in the form of upper supply and down exhaust. The temperature increased by 1 • C, and the ammonia concentration increased by 0.036 mg/m 3 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The CFD approach to the study of the spread of viral particles was used to simulate the transmission of the virus in urban public places [46,47], considering different landscape designs and air speeds, in rooms with different partitions [48][49][50][51][52], risks assessment [53][54][55], and construction drainage pipes [56]. Options for optimizing ventilation and air The factors that provide a comfortable microclimate and the theoretical foundations for modeling the microclimate in cabins based on the balance equations of heat flows are presented in [1][2][3][4][5], "the processes of convective heat exchange with the environment are described" [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The CFD approach to the study of the spread of viral particles was used to simulate the transmission of the virus in urban public places [46,47], considering different landscape designs and air speeds, in rooms with different partitions [48][49][50][51][52], risks assessment [53][54][55], and construction drainage pipes [56]. Options for optimizing ventilation and air conditioning systems are considered, including the spread of a part of the virus in buildings [57], buses and trains [58,59], and in two-phase flow systems [60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%